GINGER CANDY CONSUMPTION AND ITS IMPACT ON FIRST TRIMESTER NAUSEA - Vannisa , Rania Putri; Yanik Purwanti (PT. Antis International Publisher, 2024)
Pregnancy brings changes to a woman's body, including in the digestive system which can cause nausea and vomiting, which generally occurs in the first trimester. Morning sickness is a common complaint in pregnancy, but there are also more severe conditions, such as hyperemesis gravidarum. Treatment for nausea and vomiting can be done with pharmacological or non-pharmacological therapy. Ginger, with its antiemetic properties, is a popular choice. Ginger candy is an effective way to consume ginger to reduce nausea and vomiting in first trimester pregnant women. Ginger steeping has also been proven effective in reducing symptoms of nausea and vomiting in first trimester pregnant women. This study aims to analyze the effect of giving ginger candy on nausea and vomiting in pregnant women. This research is a national literature review that was searched using Google Scholar with the keywords